﻿Capitojoppa, a new genus of Ichneumoninae (Hymenoptera, Ichneumonidae) from Peruvian Amazonia - Claridge Brandon R; Kaunisto Kari M; Sääksjärvi Ilari E (Pensoft Publishers, 2026)
A new monotypic genus of ichneumonine parasitoid wasps (Hymenoptera, Ichneumonidae, Ichneumoninae) is described from Peru; Capitojoppagen. nov. is described to accommodate Capitojoppaamazonicasp. nov. The new genus is morphologically very distinctive and can be easily separated from all known ichneumonine genera. By describing Capitojoppa from the lowland rain forests of Peru, we aim to draw attention to the considerable diversity and morphological variation of the Amazonian ichneumonine fauna.